Design and Optimization of Trapezoidal Steering Mechanism based on Improved Particle Swarm Algorithm - Jianhua Zhai; Laiqi Qiu; Xiaohua Wei; Dongshan Yang (Jixie chuandong)
In order to make the steering mechanism characteristic curve of the wheeled mobile robot closer to the ideal Ackerman steering characteristic curve and achieve precise steering purpose， the design and parameter optimization of its steering mechanism are optimized. The design of the trapezoidal steering mechanism and its effect on the mobile robot are studied， and the nonlinear optimization model of the trapezoidal steering mechanism is established. The traditional particle swarm optimization algorithm is introduced into the adaptive weights and Lagrange interpolation method to improve the algorithm. The method of solving the optimization model of nonlinear steering mechanism is given， the M-file of Matlab R2018b with improved particle swarm algorithm and solving the nonlinear model is written to analyze the optimization of steering mechanism. The angle of the knuckle arm and wheel， the angle of the triangle rocker arm and the chassis， the size of the triangle rocker arm and the knuckle arm are determined. The results of the optimized steering mechanism are close to the ideal Ackerman steering mechanism. Finally， the optimized steering mechanism is verified by an example. The experimental results are consistent with the actual application requirements. The error between the trajectory of the steering mechanism and the ideal running trajectory can be effectively reduced， and the maneuverability and track control of the mobile robot can be improved.